Liminarités, fissures et réécritures : un événement à la frontière entre le nord du Portugal et la Galice - Paula Godinho (Cahiers de Civilisation Espagnole Contemporaine)
The border area between Portugal and Spain has long suffered from the attraction towards centers : Lisbon and Madrid. At the same time, it was a shelter area, a place to form ties ; it was another way to survive or make a living. Local history, language and sociability reveal a reality rolled out with time through coexisting local populations, either quarrelling or cooperating beyond or against the state’s norms and jurisdictions. The border is also a liminal area with its own baseness. In this text, I will examine an event that took place at the border between north Portugal and Galicia. Liminality in time and space unveils questions about remembrance policies regarding Iberian dictatorships and historicity regimes. In this case study, the event occurs in a border village, ten years after the Alzamiento : Cambedo da Raia is surrounded and under several mortar attacks, people are killed, a man commits suicide, several other people are arrested and some among these latter are sent to the dreadful Tarrafal concentration camp. Information about these events has been covered up and distorted by Portuguese censorship.